EFFICIENCY OF ASPERGILLUS TERREUS TO SOLUBILIZE INSOLUBLE FORM OF PHOSPHORUS INTO SOLUBLE FORM UNDER VARIOUS CULTURAL CONDITIONS - S. ANITHA; S.N. PADMA DEVI (International Journal of Pharma and Bio Sciences, 2016)
Phosphorous forms the second major nutrient required by the plants for its growth. It is supplied to the plants in the form of synthetic fertilizer which gets accumulated in the soil due its conversion into unavailable form. Transformation of unavailable form of phosphorus (P) to an available form becomes inevitable due to its physiological and biochemical role in plants. Since its deficiency results in the cessation of plant growth, supplementation of soluble form of phosphorus becomes essential. Fungus has the capability to convert insoluble form of phosphorus to soluble form through the secretion of organic acid as one of the solubilization mechanism. Thus in the present study, Aspergillus terreus was isolated from the rhizospheric soil sample of tomato field and was tested for its phosphorus solubilization efficacy by Broth assay method. The strain showed highest solubilization (7.5 mg/l) at the 10th day of incubation with the pH drop of 4.0. Solubilization efficacy of the isolate was high due to the secretion of organic acid (gluconic acid) which was confirmed by HPLC method. Effect of various parameters such as Carbon sources, Nitrogen sources, pH and Temperature on the solubilization of phosphorus by A. terreus was also tested. The strain showed maximum solubilization in the presence of fructose as carbon source, ammonium sulphate as a nitrogen source, at the temperature of 30ËšC and at the pH of 7.0 in both qualitative and quantitative assays. Thus A. terreus shall be used as a viable Bioinoculant to eradicate P- deficiency in plants.